If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 32 + -8j = 4(j + -4) Reorder the terms: 32 + -8j = 4(-4 + j) 32 + -8j = (-4 * 4 + j * 4) 32 + -8j = (-16 + 4j) Solving 32 + -8j = -16 + 4j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-4j' to each side of the equation. 32 + -8j + -4j = -16 + 4j + -4j Combine like terms: -8j + -4j = -12j 32 + -12j = -16 + 4j + -4j Combine like terms: 4j + -4j = 0 32 + -12j = -16 + 0 32 + -12j = -16 Add '-32' to each side of the equation. 32 + -32 + -12j = -16 + -32 Combine like terms: 32 + -32 = 0 0 + -12j = -16 + -32 -12j = -16 + -32 Combine like terms: -16 + -32 = -48 -12j = -48 Divide each side by '-12'. j = 4 Simplifying j = 4
| (4+x)2= | | 0.1(x-16)=0.6(x-1) | | 4a^2+7a-3=0 | | 19x-5=7+15x | | -(2-7x)= | | W+w+12=40 | | 2x^2-9x+9= | | 1/9(n+4/5)=-4/5(n+3/4) | | 2+3y=-1 | | 6a+(a+4)=(6a+a)+4 | | -3(x+9)=-45 | | m+5m+11=47 | | -2y+10=-3(2y+2) | | (7x+4)(2x^2-17x-9)= | | 0=-1.5a+3 | | -(7x-2)= | | -2(7w+6)=-14w+4 | | x+(x+25)+(3x)=435 | | -2(2+x)=-2x+1 | | -6x^2+15x=-7x-21 | | 48+8x=10x-6 | | n(n-1)(n-2)=0 | | 2x^2-7x+111=0 | | 3x^2-8x-11= | | -14a+6=12a-20 | | 5g-2g=45-2g | | A(b-6)= | | 4x^3+28x^2-120x=0 | | 3(x-2)+6=38.85 | | 5y-5=-2y+2 | | -2(3x-4)+12=28 | | 1.9+9.3=n+54.7 |